The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3233/jpd-202351
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Limit Accumulation of Aggregate Pathology Following Intrastriatal Injection of α-Synuclein Fibrils

Abstract: Background: α-Synuclein (α-syn) is the predominant protein in Lewy-body inclusions, which are pathological hallmarks of α- synucleinopathies, such as Parkinson’s disease (PD) and multiple system atrophy (MSA). Other hallmarks include activation of microglia, elevation of pro-inflammatory cytokines, as well as the activation of T and B cells. These immune changes point towards a dysregulation of both the innate and the adaptive immune system. T cells have been shown to recognize epitopes derived from α-syn and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 79 publications
5
30
0
Order By: Relevance
“…To determine if the microglia detection model can be effectively adapted to quantify microglial activation across labs, histopathological slides from a different mouse model of αSyn aggregation were used. This model, based on the intrastriatal injection of αSyn PFFs, is characterized by changes in microglia morphology with minimal effects on the total number of cells, a finding that is consistent with mouse models using intrastraital injections of AAVs to produce αSyn aggregation [18,24].…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…To determine if the microglia detection model can be effectively adapted to quantify microglial activation across labs, histopathological slides from a different mouse model of αSyn aggregation were used. This model, based on the intrastriatal injection of αSyn PFFs, is characterized by changes in microglia morphology with minimal effects on the total number of cells, a finding that is consistent with mouse models using intrastraital injections of AAVs to produce αSyn aggregation [18,24].…”
Section: Resultssupporting
confidence: 76%
“…To evaluate how well our new microglia detection model quantifies microglia activation we compared area/perimeter ratios between our model and a custom semi-automated object-segmentation MATLAB script that has been previously published[18,24]. Using histological slides from the αSyn induced olfactory dysfunction model, we analyzed 3 brain regions across 4 mice and compared the values of all cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, despite most studies indicate that T-cell mediated autoimmune response to αSyn plays a detrimental role in the physiopathology of Parkinson's disease, there is also evidence indicating that T-cell response might be beneficial under some circumstances. For instance, it has recently been shown that the transfer of T-cells into immunodeficient mice (NOD SCID gamma-chain deficient, NSG) reduces the deposits of phospho-S129-αSyn, one of the pathogenic forms of αSyn, in the striatum and frontal cortex in a model of Parkinson's disease induced by the injection of hαSyn preformed fibrils (PFF) into the striatum [29].…”
Section: Role Of T-cells In the Development Of Neuroinflammation And Neurodegeneration Involved In Parkinson's Diseasementioning
confidence: 99%